Comparative evaluation of 2-isopropyl-3-methoxypyrazine, 2-isobutyl-3-methoxypyrazine, and 2, 4, 6-trichloroanisole degradation by ultraviolet/chlorine and ultraviolet/hydrogen peroxide processes. (September 2021) - Lee, Juwon; Nam, Sook-Hyun; Koo, Jae-Wuk; Kim, Eunju; Hwang, Tae-Mun
Abstract: 2-Isopropyl-3-methoxypyrazine (IPMP), 2-Isobutyl-3-methoxypyrazine (IBMP), and 2, 4, 6-Trichloroanisole (TCA) are the primary emerging taste and odor (T&O) compounds in water systems with low thresholds (ng L −1 ). The selected T&O compounds are known to be difficult to remove using conventional water treatment processes. In this study, we compared the removal characteristics of the three T&O compounds using UV/Cl2 and UV/H2 O2 . The removal rates of the three compounds by direct photolysis at 254 nm were less than 10%, even at a high UV dose (approximately 1000 mJ cm −2 ). Under conditions of an oxidant injection volume of 5 mg L −1 and UV dose of 1000 mJ cm −2, the degradation rate of the target compounds in the UV/H2 O2 process exceeded that of the UV/Cl2 process. Moreover, the results revealed that pH has a significant impact on the removal of the T&O compounds during the UV/Cl2 process. The IPMP, IBMP, and TCA were found to be more reactive with hydroxyl radicals than reactive chlorine species (RCS). A predictive tool was developed to determine the optimal operating condition using the generalized reduced gradient (GRG) nonlinear solver. In the UV/H2 O2 process, the EED value for 90% removing rate was 0.156 kWh m −3 for the IPMP, 0.135 kWh m −3 for the IBMP, and 0.154 kWh m −3 for the TCA, respectively. In case of the UV/Cl2, the EED value for 50% removing rate was 0.174 kWh m −3 for the IPMP, 0.138 kWh m −3 for the IBMP, and 0.169 kWh m −3 for the TCA, respectively. Highlights: The IPMP, IBMP, and TCA were found to be more reactive with hydroxyl radicals than RCS. UV/H2 O2 process was more effective in degrading IPMP, IBMP, and TCA compounds present in water systems. The optimal operating conditions to achieve the target removal rate in the UV/H2 O2 and UV/Cl2 processes were compared (Bruce et al., 2002) using the kinetic model and GRG nonlinear solver algorithm.